Crise climática e antropoceno: perspectivas ecofeministas para liberar a vida - Colerato, Marina Penido (2023)
This research analyzed how ecofeminist praxis can collaborate to build ecological and anti-patriarchal societies in the face of the intensification of the climate crisis and the increase in violence against women in the neoliberal context, highlighting the interconnectedness of both phenomena. The global climate agenda's low success in reducing emissions and promoting ecological justice, and the relationship of this agenda with the expansion of markets and the financialization of nature, were analyzed along with the post-political narrative of the popular Anthropocene, in which class contradictions figure peripherally. Using ecofeminist epistemology and historical materialism, the objective was to evaluate the hypothesis that the climate crisis is one expression of the depletion of capitalist value relations sustained by a tripartite class formed by women, nature/colonies, and free workers (Femitariat, Biotariat, Proletariat) and a consequence of a patriarchal capitalist society which ignores the material and ecological reality of its own embodied and embedded existence. It analyzed the ecofeminist perspectives in the praxis of Jineolojî of the Kurdish Women's Movement from an ecofeminist proposal based on: i) the ecofeminist argument that there is a relationship between the subordination of women and the exploitation of nature, ii) the need raised by deep ecology for a non-anthropocentric cosmology and ontology and, iii) the Marxist analysis of the dialectic relations between humans and material life based on the Feminist Participatory Action-Research methodology proposed by sociologist Maria Mies (1996). The results confirmed the hypothesis that women, nature, and "colonies" exploitation is a historical material necessity and that the global agenda for "development" and "green economy" has been used to make the accumulation process viable in the face of profit stagnation. It concluded by suggesting the way to dismantle such value relationships forged to enable unsustainable infinite development and progress is to demand women’s liberation. It also showed how the Kurdish Women's Movement, in line with ecofeminist praxis, is building autarchic, ecological, and anti-patriarchal communities centered on the production of life, albeit within an unfavorable context; case of Jinwar, the Village of free women in Rojava. Combined with local women's struggles in countries of the global North and South from a peoples' diplomacy perspective, the case study offered renewed possibilities for the anti-patriarchal and ecological struggles in the 21st century